INCREASING THE EFFICIENCY OF LEARNING LATIN LANGUAGE STUDENTS THROUGH THE DEVELOPMENT OF LINGUODIDACTIC THINKING IN HIGHER MEDICAL EDUCATIONAL INSTITUTIONS - Bakaev Najmiddin (Bright Mind Publishing, 2025)
This article describes the issue of formation of indicators for the assessment of the quality of Latin language teaching to students of medical higher educational institutions, in particular, the analysis of the issue of indicators and criteria for evaluating the process of Latin language teaching.
Keywords: Linguodidactic, education, technology, thinking, development, problems.